PENGARUH PEMBERIAN BUBUK EKSTRAK CU-TURUNAN KLOROFIL DAUN CINCAU (Premna oblongijolia Merr.) TERHADAP PROFIL LIPID DARAH KELINCI - Nurdin Nurdin; Ali Khomsan; Sri Anna Marliyati; Faisal Anwar; Clara Meliyanti Kusharto; Dewi Ratih Agungpriyono (Media Gizi dan Keluarga, 2008)
ABSTRACT. The aim of this research was to produce cincau copper-derivative chlorophyll powder and to observe its phYSico-chemical properties and the effect on blood lipid profile of5 month male New Zealand White rabbits. The blood lipid profile observed were total cholesterol, triglyceride, HDL (high-denSity lipoprotein) cholesterol, and LDL (low-density lipoprotein) cholesterol. A two months treatment was conducted A randomblock design was applied with the following treatment on each experimental unit: PO (basal diet, negative control), PI (basal diet with cholesterol 0.1% (wlw) added, positive control), P2 (basal diet with cholesterol 0.1% (wlw) and 16.7 mglkg-body weight/d natural chlorophyll powder added), P3 (basal diet with cholesterol 0.1% (wlw) and 16.7 mglkgbody weight/d copper-derivative of chlorophyll powder added), P4 (basal diet withcholesterol 0.1% (wlw) and 50.1 mglkg-body weightld copper-derivative of chlorophyll powder added}, P5 (basal diet with cholesterol 0.1% (wlw), and 16.7 mglkg-body weight/dcommercial chlorophyll powder added The results of study showed that cincau leaves chlorophyll extract solution with Cu1+ 100 mglL level produce the cincau copper-derivate chlorophyll powder with highest pH, solubility, and greenness compared to other copper levels. Feeding with copper-derivative of chlorophyll cincau powder (P3) most likely decreased total cholesterol, triglycerides, LDL cholesterol increased the HDL cholesterol,and decreased atherosclerosis risk after 2 month as compare to feeding contain of natural chlorophyll (P2). Keywords: Premna oblongifolia Merr., copper-derivate chlorophyll powder, totalcholesterol, triglyceride. HDL cholesterol, LDL cholesterol